Menstrual dysfunction in swimmers - Constantini, N. W.; Warren, M. P. (The Journal of Clinical Endocrinology & Metabolism, 1995)
The menstrual status of swimmers (N = 69; age = 16.9 yr) was investigated and compared to 279 age-matched controls. Age of menarche was significantly delayed among simmers (+.8 yr). Swimmers (82%) had more menstrual irregularities after menarche compared to controls (40%). Levels of dehydroepiandrostedione sulfate and androstenedione, but not testosterone, were higher than average in all age-groups of swimmers. This hormonal profile is different from the hypothalamic amenorrhea described for dancers and runners. It suggests a different mechanism for reproductive dysfunction in swimmers that is not associated with hypoestrogenism, but rather, with hyperadrogenism. A distinction among the various types of athletic amenorrhea should be made. Implications. Female competitive swimmers are vulnerable to delayed puberty and menstrual irregularities. The reasons for these occurrences are probably different to other sports and specific to swimming. (Journal of Clinical Endocrinology Metabolism, 80, 2740-2744)